The world is open : how Web technology is revolutionizing education - Bonk, Curtis Jay.; Wiley InterScience (Online service) (San Francisco, Calif. : Jossey-Bass ; Chichester : John Wiley [distributor], 2011)
Annotation To help educators understand what's possible, Curt Bonk employs his'WE-ALL-LEARN' model to outline ten key technology and learning trends, demonstrating how technology has transformed educational opportunities for learners of every age in every corner of the globe.
Front Matter -- Introduction to the Open Learning World -- We All Learn -- To Search and to Scan: Opener #1: Web Searching in the World of E-Books -- E-Demand Around the Globe: Opener #2: E-Learning and Blended Learning -- It's a Free Software World After All: Opener #3: Availability of Open Source and Free Software -- MIT in Every Home: Opener #4: Leveraged Resources and Open Course Ware -- Portals for the People: Opener #5: Learning Object Repositories and Portals -- Making a Contribution: Opener #6: Learner Participation in Open Information Communities -- Collaborate or Die!: Opener #7: Electronic Collaboration and Interaction -- Who Are You?: Opener #8: Alternative Reality Learning -- U-Learning?: Opener #9: Real-Time Mobility and Portability -- Learning at Your Service: Opener #10: Networks of Personalized Learning -- The Treasures and Traps of This Open Learning World -- Acknowledgments -- Postscript: An Open Letter to the Learners of this Planet -- The Author -- Endnotes -- Index.
Originally published: 2009.
Includes bibliographical references and index.
Print version record.
Keywords: Internet in education; Internet in education; Electronic books